Motivational factors for recreational fishing, the profile and life satisfaction level of recreational fishers and nonparticipants of fishing in Turkey - Faik Ardahan; Tevfik Turgut (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to examine the profile and the life satisfaction (LS) of male Recreational Fishers (RF) and to find out the motivational factors for participating in recreational fishing (RFG) in Turkey and compare the LS of RF and non-participants of recreational fishing (NPF). The sampling of this study consisted of 359 RF, 284 NPF, totally 643 participants. As a result of this study, it was found that the major factors motivating for fishing are “commune with nature”, “relaxation”, “to affect health positively”, “to get away from demand”, and “to be happy”. It was found that the factors motivating for fishing have statistically meaningful correlations with demographic variables and LS as well as each other and there are statistically meaningful differences among groups of the demographic variables as marital status, occupation, and with whom one goes for fishing, RF and NPF. Namely, strength of the factors motivating people for fishing is dependent to the demographic variables. Furthermore, it was found statistically meaningful correlations between LS and the demographic variables.